PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK THRIFT DAN DAMPAKNYA TERHADAP KEPUASAN KONSUMEN PADA YOUTH THRIFT MARKET DI KOTA PALU - Elimawaty Rombe; Neng Reka Nurmalasari; Syamsul Bachri; Mohammad Zeylo Auriza (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of Instagram social media marketing and price on thrift product purchasing decisions and their impact on customer satisfaction at the Youth Thrift Market in Palu City. The type of research used is descriptive quantitative. The sampling technique in this study used a purposive sampling method. The sample used was 80 respondents. The data collection technique used was distributing questionnaires and processed using Smart PLS version 3.0. The scale used in this study is the Likert scale. The analysis technique used is descriptive statistics which consists of direct and indirect influence variables and is supported by Patrial Least Squares (PLS) which consists of two approaches, namely Outer Model and Inner Model analysis. The results of this study indicate that significantly social media marketing Instagram has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, purchasing decisions have a positive and significant effect on consumer satisfaction, social media marketing Instagram has a positive and significant effect on customer satisfaction through purchasing decisions, prices have a positive and significant effect on consumer satisfaction through purchasing decisions. There is a positive but not significant influence between Instagram social media marketing on consumer satisfaction and price on consumer satisfaction.